Numerical and experimental investigation of a thermosiphon solar water heater system thermal performance used in domestic applications. Issue 5 (30th March 2021) - Jasim, Ayoob Khalid; Freegah, Basim; Alhamdo, Mohammed Hamed
Abstract: The thermosiphon is a passive heat exchange method, which circulates a fluid within a system without the need for any electrical or mechanical pumps. The thermosiphon is based on natural convection where the thermal expansion occurs when the temperature difference has a corresponding difference in density across the loop. Thermosiphons are used in different applications such as solar energy collection, automotive systems, and electronics. The current study aims to investigate thermosiphon thermal performance used in domestic applications. The thermal performance of a thermosiphon has been studied by many researchers; however, according to the knowledge of the authors, the influence of the amount of the working fluid on the thermal output has not yet been investigated. Therefore, the influence of the amount of working fluid within the riser pipe has been investigated on the thermal performance of the thermosiphon. In the current study, a computational fluid dynamics model is involved. This model has been validated by comparison with experimental findings. The maximum variation between numerical and experimental results is 14.2% and 11.2% for the working fluid at the inlet and outlet of the absorber pipe, respectively. Furthermore, the results show that the amount of working fluid inside the closed thermosiphon has a great influence on the thermal performance of the system. Additionally, it is found that Case‐B, when the amount of working fluid is less than by 10% compared to the traditional model, is the best case among all cases under study. Furthermore, a correlation equation to predict water temperature at the exit of the absorber pipe has been established with an accuracy of 95.05%.